Whatever we should know about inflammatory bowel diseases - Asemi, S (Iran University of Medical Sciences, 1998)
Inflammatory bowel diseases are a general term for a group of chronic inflammatory diseases with unknown etiology that involve gastrointestinal system. The diagnosis of these diseases is possible with rule out of other diseases because there are not special diagnostic tests for them. Nevertheless, clinical feature of these diseases are very specific and in most cases definite diagnosis are possible. Inflammatory bowel diseases are divided in two grand groups: ulcerative colitis and crohn's disease. Epidemiologic and etiologic background of these two groups is similar and must be discussed together. These diseases are most prevalent in Caucasians and Asian race people. Also, these diseases in Jewish people are three to sixth time more than the others and in two genders are equal